The Power of Images, Reconsidered - Thompson, Erin L. (Revista Concinnitas, 2021)
This essay reappraises David Freedberg’s foundational The Power of Images: Studies in the History and Theory of Response (University of Chicago Press, 1989), in light both of his more recent publications on iconoclasm, censorship, and the role of irrational and emotional responses to images in general and of the current global wave of iconoclastic actions. Keywords: neuroaesthetics; emotion; censorship; universality